Autotransplantation, Surgical Repositioning of Retained Canine, and Apical Filling of Two Incisors with Root Resorption - Juarez Broon, Norberto; Bello Hernandez, Cuauhtemoc; Ruiz MontaÃ±ez, Oscar Ivan; Diaz Rosales, Elizabeth; Padron Santana, Jaime; Calderon Escamilla, Alejandra Zulema (Iranian Endodontic Journal, 2018)
The purpose is to show the autotransplantation and surgical repositioning of a retained canine, and the apical filling of central and lateral resorbed incisors from a 12-year-old female patient, healthy and with clinical absence of left maxillary canine. Radiographically, the retained canine between the resorbed central and lateral incisors was observed. Root canal treatment of the canine was performed after 8 weeks; apical curettage and placement of bovine graft in inter-incisal zone was done after 4 months. During 6 months, orthodontic traction of the canine was carried out with no positive results, and 12 months after the autotransplantation, surgical repositioning was performed. Clinical-radiographic control at 30 days and 24 months showed absence of inflammation, restoration and integration of the tooth-supporting structures. Autotransplantation combined with surgical repositioning of the retained canine and the apical filling of two incisors achieved the harmonious, aesthetic, functional, dental and psychological preservation of the patient. Keywords: Autotransplantation; Endodontics; Endodontic Surgery; Root Resorption; Surgical Repositioning